Beyond the diagnosis of cystic fibrosis: a study of disease-related knowledge in patients and their families - Henley, Lesley D (Department of Health Sciences Education, 2026)
A cross-sectional survey was conducted among 60 families with a child with cystic fibrosis (CF) to assess their medical knowledge of the illness, their subjective understanding of the patient's present and future health, how much they wanted to be told about the illness, their information needs and sources and to identify important sociodemographic and medical correlates of these assessments. The study also examined the relationship between knowledge of CF and personal and family adjustment. The sample comprised all CF patients, within the Western Cape Hospital Region, who had attended the Red Cross War Memorial Children's Hospital in Cape Town over a two year period. Data were collected by means of structured questionnaires administered to 54 fathers, 60 mothers, 18 patients (aged 9-22 years) and 29 siblings (10-23 years). Respondents completed the questionnaires in their homes. A 63 item multiple choice test, with acceptable psychometric properties, was used to assess medical knowledge. Parents and patients correctly answered approximately three-quarters, and siblings two-thirds, of the items. Mothers were slightly, yet significantly, better informed than fathers and siblings were significantly less informed than parents and patients. Family members were most knowledgeable about general CF facts, physiotherapy, gastrointestinal symptomatology and treatment and anatomy. They were less well-informed about respiratory symptomatology and treatment and nutrition. Parental knowledge of genetics and reproductive risks was mediocre, while that of patients and siblings was poor. Family members were least knowledgeable about general medical facts and terminology. Misconceptions, gaps and errors in CF knowledge, which could lead to inadvertent non-compliance, were identified. Single item ratings of the patient's present and future health revealed highly positive perceptions among all respondents. Index ratings of information preferences showed that most family members wanted complete and comprehensive information about CF. Measures of family members' information needs indicated that, in general, they wanted less information about symptomatology, treatment and genetics and more information about the psychosocial and future implications of CF. Fathers and siblings desired more medical information than mothers and patients. Parents and patients relied most often on CF clinic doctors, their spouse/parents, prayer and faith and CF literature for information and guidance about the illness. Used less frequently were the CF Association and other parents with a CF child, while the hospital physiotherapists, social worker, dietician, the family doctor, local pharmacist and priest/minister were the least used sources. Siblings depended on mothers for their CF information. Based on index ratings of communication problems, most parents and patients did not experience difficulties when seeking information from the clinic doctors. Among a minority, the tendency to forget what they were told, a lack of privacy at the clinic and use of jargon presented problems. Parental index ratings of communication problems were inversely related to their CF knowledge. Among parents, only social class was significantly associated with CF knowledge, perception of the patient's future health, magnitude of information needs, receipt of CF information, use of selected sources of information and the experience of communication problems with doctors. Information preferences were independent of social class. social class effect was not noted for patients and siblings. Parents who obtained higher scores on the test of CF knowledge and had lower information needs also reported less self-rated anxiety and depression. Findings suggest the need for an ongoing assessment of parents' and patients' CF knowledge to identify areas of ignorance and to dispel misconceptions. The medical team needs in addition, to recognize that most family members want maximum information about CF and far more information about its psychosocial and future implications. The lower levels of CF knowledge and higher information needs of parents from the lower social classes warrant further consideration by health care professionals.